Crime and racial constructions: cultural misinformation about African Americans in media and academia - Covington, Jeanette (Lexington Books, 2010)
Introduction : crime and racial constructions -- Images of black male criminality in media and the social sciences. Black images in the post-civil rights era -- Hollywood and black protest : the rise of ghetto action movies -- Black violence, white violence : cinematic images of the urban underclass -- Making race matter : how criminologists look at African Americans and violence -- Americanizing black violence : making criminology race-free -- Cinematic and academic images of black female criminals and victims. Black women on the silver screen -- Black women, violence and masculinization -- Comforting fictions: black women, Hollywood and color-blind racism